Comparison of internal medicine applicant and resident characteristics with performance on ACGME milestones - Alex G. Ryden; Trent C. Fuller; Richard S. Rose; Katie L. Lappe; Sonja Raaum; Stacy A. Johnson (Medical Education Online, 2023)
ABSTRACTInternal medicine (IM) residency programs select applicants based on several metrics. Factors predicting success during residency are unclear across studies. To identify whether specific applicant or resident factors are associated with IM resident performance using ACGME milestones. We tested for associations between applicant factors available prior to the start of IM residency and resident factors measured during IM residency training, and resident performance on ACGME milestones across three consecutive years of IM training between 2015-2020. Univariable and multivariable linear regression modeling was used to test associations. Eighty-nine categorical IM residents that completed 3 consecutive years of training were included. Median age was 28 years (IQR 27-29) and 59.6% were male. Mean ACGME milestone scores increased with each post-graduate year (PGY) from 3.36 (SD 0.19) for PGY-1, to 3.80 (SD 0.15) for PGY-2, to 4.14 (SD 0.15) for PGY-3. Univariable modeling suggested referral to the clinical competency committee (CCC) for professionalism concerns was negatively associated with resident performance during each PGY. No applicant or resident factors included in the final multivariable regression models (age at starting residency, USMLE Step scores, interview score, rank list position, ITE scores) were associated with ACGME milestone scores for PGY-1 and PGY-2. Referral to the CCC for professionalism was negatively associated with resident performance during PGY-3. Residency selection factors did not predict resident milestone evaluation scores. Referral to the CCC was associated with significantly worse resident evaluation scores, suggesting professionalism may correlate with clinical performance.